Modulating Targeting of Poly(ethylene glycol) Particles to Tumor Cells Using Bispecific Antibodies. Issue 9 (14th March 2019) - Cui, Jiwei; Ju, Yi; Houston, Zachary H.; Glass, Joshua J.; Fletcher, Nicholas L.; Alcantara, Sheilajen; Dai, Qiong; Howard, Christopher B.; Mahler, Stephen M.; Wheatley, Adam K.; De Rose, Robert; Brannon, Paul T.; et al.
Abstract: Low‐fouling or "stealth" particles composed of poly(ethylene glycol) (PEG) display a striking ability to evade phagocytic cell uptake. However, functionalizing them for specific targeting is challenging. To address this challenge, stealth PEG particles prepared by a mesoporous silica templating method are functionalized with bispecific antibodies (BsAbs) to obtain PEG–BsAb particles via a one‐step binding strategy for cell and tumor targeting. The dual specificity of the BsAbs—one arm binds to the PEG particles while the other targets a cell antigen (epidermal growth factor receptor, EGFR)—is exploited to modulate the number of targeting ligands per particle. Increasing the BsAb incubation concentration increases the amount of BsAb tethered to the PEG particles and enhances targeting and internalization into breast cancer cells overexpressing EGFR. The degree of BsAb functionalization does not significantly reduce the stealth properties of the PEG particles ex vivo, as assessed by their interactions with primary human blood granulocytes and monocytes. Although increasing the BsAb amount on PEG particles does not lead to the expected improvement in tumor accumulation in vivo, BsAb functionalization facilitates tumor cell uptake of PEG particles. This work highlights strategies to balance evading nonspecific clearance pathways, while improving tumor targeting and accumulation. Abstract : Bispecific antibodies can be attached to poly(ethylene glycol) (PEG) particles via a one‐step process, resulting in stealth PEG particles with targeting ability to tumor cells. The amount of bispecific antibody on the particle surface plays an important role in tumor cell targeting and organ distribution of the targeted stealth particles.